2003
DOI: 10.1002/bem.10135
|View full text |Cite
|
Sign up to set email alerts
|

Waveform magnetic field survey in Russian DC and Swiss AC powered trains: A basis for biologically relevant exposure assessment

Abstract: Recent epidemiological studies suggest a link between transport magnetic fields (MF) and certain adverse health effects. We performed measurements in workplaces of engineers on Russian DC and Swiss AC powered (16.67 Hz) electric trains using a computer based waveform capture system with a 200 Hz sampling rate. MF in DC and AC trains show complex combinations of static and varying components. The most probable levels of quasistatic MF (0.001-0.03 Hz) were in the range 40 microT. Maximum levels of 120 microT wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, the µT in AC locomotives. In addition, they reported SMF of 0.4 mT in DC-powered transport systems (14). These results are in line with the findings of the current study presented in Table 1.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, the µT in AC locomotives. In addition, they reported SMF of 0.4 mT in DC-powered transport systems (14). These results are in line with the findings of the current study presented in Table 1.…”
Section: Discussionsupporting
confidence: 83%
“…Although in their study, the ELF-MF and SMF values were higher than those of the present research were, the amounts still did not exceed the recommended occupational limits. Moreover, Ptitsyna et al found that SMF is the major portion of the MF encountered on board Russian DC powered transport systems rather than AC locomotives (14). However, the SMF values in Ptitsyna et al and Nakagava and Koanas' research and other relevant studies were ten times the amount of the background level (30 to 60 µT (19)).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Intensity of industrial magnetic fields can amount up to 120 μT, but contribution of the industrial (artificial) magnetic fields in total average intensity of environmental magnetic field is rather small because of mutual compensation (cancellation) of industrial magnetic fields [84,85]. …”
Section: Brief Summary Of Our Knowledge About Geomagnetic Field Its mentioning
confidence: 99%